394 An Anatomy Near-Peer Teaching Programme. (4th May 2021) - Stubley, T; Taylor, J
Abstract: Introduction: The time dedicated to teaching of anatomy in medical schools, as well as the importance placed upon it, is decreasing. Many students struggle with learning the vast quantity of information necessary and few medical students receive instruction on how to teach. A near-peer teaching programme was designed to allow tutors to develop vital teaching skills and provide tutees with a closer look at the more complicated aspects of the anatomy course. Method: Sessions took place once or twice a week throughout the academic year and were subdivided into examination technique sessions, core anatomical knowledge sessions and prosection sessions. Tutors were recruited primarily from the intercalated Clinical Anatomy BSc. Tutees were provided anonymous feedback forms following each session and completed pre and post session MCQ tests. Tutors completed a feedback form following the programme's completion. Results: 96.9% of students reported an improvement in understanding of the topic. Students reported an increase in how prepared they felt for examinations (p < 0.001) as well as an improvement in MCQ scores (p < 0.001). 93.8% of tutors stated the programme helped prepare them for future teaching. Conclusions: The results of this programme strongly support the use of near-peer teaching in anatomy education, with clear benefits for tutors and students.